2015
DOI: 10.1245/s10434-015-4368-8
|View full text |Cite
|
Sign up to set email alerts
|

Standard Versus Extralevator Abdominoperineal Low Rectal Cancer Excision Outcomes: A Systematic Review and Meta-analysis

Abstract: Our analysis confirms the oncological advantages of the extended abdominoperineal excision method. Although the perineal wound complications were higher, the length of postoperative hospital stay was shorter, and quality of life was not inferior to the conventional resection method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 63 publications
2
34
0
1
Order By: Relevance
“…We observed a higher incidence of perineal wound morbidity in the ELAPE arm. Although some earlier reports mention that delayed perineal wound healing is significantly higher after ELAPE than after an APE , a few others report comparable perineal wound morbidity . The uniform use of NCRT in our study would have further contributed to the delayed healing of the perineal wound.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…We observed a higher incidence of perineal wound morbidity in the ELAPE arm. Although some earlier reports mention that delayed perineal wound healing is significantly higher after ELAPE than after an APE , a few others report comparable perineal wound morbidity . The uniform use of NCRT in our study would have further contributed to the delayed healing of the perineal wound.…”
Section: Discussionmentioning
confidence: 56%
“…The lack of statistical significance is probably a result of the small sample size. Whilst two meta-analyses have shown that CRM involvement is significantly reduced after an ELAPE [19,20], two others have shown no significant difference [21,22]. As photography of specimens and independent histopathological evaluation was not performed in these studies, it is not possible to determine the quality of either the ELAPE or the CAPE procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The high prevalence of perineal wound breakdown after ELAPE results from the wide cavity, the accumulation of fluids, and the effects of preoperative radiotherapy [13][14][15]. Wound morbidity ranges from asymptomatic seroma to a painful non-healing perineal wound.…”
Section: Discussionmentioning
confidence: 99%
“…Development of more radical techniques for advanced tumours, e.g., extralevator APE has led to improved clinical outcomes in some studies through a reduction in CRM involvement and perforations compared to "conventional" APE surgery [7,21,22] . Extralevator APE involves the removal of the levator ani with the mesorectum and anal sphincters, creating a more cylindrically shaped specimen and thereby providing critical extra tissue around a low rectal tumour [22] .…”
Section: Surgical Anatomy Of Ape Specimensmentioning
confidence: 99%